Fibroblast growth factor 23 and 25-hydroxyvitamin D levels are associated with estimated glomerular filtration rate decline - Hamano, Takayuki (Nature Publishing Group, 2013)
The combination of serum 25-hydroxyvitamin D (25D) and fibroblast growth factor 23 (FGF23) levels predict hard renal outcomes in patients with chronic kidney disease (CKD), independent of classical markers of mineral and bone disorders, including serum phosphorus, parathyroid hormone, 1,25-dihydroxyvitamin D levels, and active vitamin D therapy. In a prospective cohort study of 738 Japanese pre-dialysis outpatients with CKD, we examined potentially non-linear associations between 25D and FGF23 levels and estimated glomerular filtration rate (eGFR) changes in 727 patients with at least a 6-month observation period and no history of admission by acute kidney injury. We used multiple regression analyses with restricted cubic spline functions using annualized eGFR decline as a dependent variable. A significantly non-linear positive relationship between 25D and eGFR changes was observed. The annualized eGFR decline was greater in patients with 25D concentrations <25 and 23 ng/ml in univariate and multivariate analyses, respectively. Above this threshold, the eGFR decline plateaued. FGF23 showed a linear negative association with eGFR changes. After dividing the patients into four groups according to median 25D and FGF23 levels, the annualized eGFR changes in the Low FGF23-Low 25D, High FGF23-High 25D, and High FGF23-Low 25D groups were 0.49 (95% confidence intervals: −2.83 to 3.81), −1.24 (−5.00 to 2.52), −4.77 (−8.85 to −0.69), respectively, relative to the Low FGF23-High 25D group (P for trend, 0.02). Thus, combined use of FGF23 and 25D is useful to predict eGFR change in patients with CKD as well as hard renal outcomes.